2009
DOI: 10.1128/aem.01194-09
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Amylosucrase Variants That Terminate Catalysis of Acceptor Elongation at the Di- or Trisaccharide Stage

Abstract: An amylosucrase gene was subjected to high-rate segmental random mutagenesis, which was directed toward a segment encoding amino acids that influence the interaction with substrate molecules in subsites ؊1 to ؉3. A screen was used to identify enzyme variants with compromised glucan chain elongation. With an average mutation rate of about one mutation per targeted codon, a considerable fraction (82%) of the clones that retained catalytic activity were deficient in this trait. A detailed characterization of sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This and the TLC mobility suggested that they contain increasing numbers of Glc units. This was further supported by the results obtained when the reaction was catalyzed by one of the previously generated Ams variants (Ams-V16) that are compromised in chain elongation (Schneider et al 2009). In this case, essentially, only Cat-A1, the acceptor product with the highest TLC mobility, was formed, even after 120 h of incubation (not shown).…”
Section: Glucosylation Screening Of Flavonoidsmentioning
confidence: 52%
“…This and the TLC mobility suggested that they contain increasing numbers of Glc units. This was further supported by the results obtained when the reaction was catalyzed by one of the previously generated Ams variants (Ams-V16) that are compromised in chain elongation (Schneider et al 2009). In this case, essentially, only Cat-A1, the acceptor product with the highest TLC mobility, was formed, even after 120 h of incubation (not shown).…”
Section: Glucosylation Screening Of Flavonoidsmentioning
confidence: 52%
“…In addition to the 3 domains A, B and C common to all GH13 family members (Figure 4), AS have 2 extra domains named N and B' that are unique to these enzymes. These 3D structures have allowed the identification of key residues involved in the polymerization process, and have guided the construction of AS mutants which produce in a controlled way either short maltooligosaccharides or insoluble amylose from sucrose (Albenne et al 2004;Cambon et al 2014;Schneider et al 2009).…”
Section: Amylosucrasesmentioning
confidence: 99%